Analysing corporate political activity in MNC subsidiaries through the integration-responsiveness framework. Issue 5 (October 2019) - Banerjee, Shantanu; Venaik, Sunil; Brewer, Paul
Highlights: Our study extends market-strategy focussed integration-responsiveness (IR) framework by incorporating the non-market strategy of subsidiary CPA within a single, holistic framework. We find government regulation and the market strategies of integration and innovation have positive relationships with MNC subsidiary political activities. We identify dual and separate paths to the outcomes of performance and legitimacy. Where the market strategy of innovation has a positive effect on subsidiary performance but not on legitimacy, the non-market subsidiary political activities enhance subsidiary legitimacy but not subsidiary performance. In addition, both market innovation and non-market subsidiary political activities are useful tools to gain favourable government decisions. Overall, both market and non-market strategies play complementary role in enhancing subsidiary performance and legitimacy respectively. Abstract: Our study applies the well-known, market-strategy focussed integration-responsiveness (IR) framework and extends it to incorporate the non-market corporate political strategies of MNC subsidiaries. We find government regulation and the market strategies of integration and innovation have positive relationships with MNC subsidiary political activities. Interestingly, whereas the market strategy of innovation has a positive effect on subsidiary performance (but not on legitimacy), the non-market corporate political activities undertaken by MNC subsidiaries enhance subsidiary legitimacy (but not subsidiary performance). In addition, both market innovation and non-market subsidiary political activities are useful tools to gain favourable government decisions. Overall, our study incorporates both market and non-market strategies within a single overarching IR framework, and highlights their complementary role in achieving the twin goals of performance and legitimacy respectively.